An efficient joint spectrum and power allocation in cognitive radio networks using a modified firefly algorithm. (2017) - Tounsi, Abdelkader; Babes, Malika
In this paper, the applicability and efficiency of the new meta-heuristic algorithm called firefly algorithm to solve the joint power control and channel allocation problem in cognitive radio networks is studied. A modified version of the firefly algorithm (MFA) using the new attractiveness factor is proposed to solve the problem. Theoretical analysis is presented to prove effectiveness and the existence of Nash equilibrium of the proposed strategy. Simulation results of this study show that the proposed power control based on modified firefly algorithm cannot only able to find the optimal transmit power that maximises each secondary's own utility but also improves the fairness among secondary users and satisfies the outage probability constraints. Our results show that the proposed method outperforms previous approaches (including the standard firefly algorithm) in terms of convergence speed.